Predialysis fluid overload and gait speed: a repeated measures analysis among patients on chronic dialysis. Issue 6 (30th December 2019) - Carlos, Christopher; Grimes, Barbara; Segal, Mark; Johansen, Kirsten
Abstract: Background: Slow gait speed is associated with hospitalization and death. We examined whether predialysis fluid overload contributes to gait speed impairment. Methods: We measured predialysis gait speed at baseline and 12 and 24 months among 298 patients recruited in the A Cohort Study to Investigate the Value of Exercise in ESRD/Analyses Designed to Investigate the Paradox of Obesity and Survival in ESRD. We used multivariable linear mixed modeling to examine associations between patient data and gait speed. We then added either bioimpedance-estimated volume of predialysis fluid overload or volume of delivered ultrafiltration to ascertain whether fluid excess was associated with gait speed and its trajectory. We also tested whether fluid overload change with time was predictive of gait speeds. Results: The mean baseline gait speed was 1.01 m/s and it declined by an average of 0.08 m/s/year. Older age, nonwhite race, Hispanic ethnicity, diabetes, recent fall, recent hospitalization, tobacco use and lower serum albumin were associated with slower gait speed. Each liter of predialysis fluid overload was associated with a 0.02 m/s slower gait speed [95% confidence interval (CI) 0.01–0.04, P = 0.008] and 0.05 m/s additional slowing per year (95% CI 0.03–0.06, P < 0.0001). Higher ultrafiltration volumes were associated with 0.07 m/s slower gait speed per 3% body weight removed (0.002–0.14, P = 0.045) but not with gait speed trajectory (P = 0.08). Patients who increased fluid overload walked 0.08 m/s slower compared with those who decreased fluid overload (95% CI 0.003–0.15, P = 0.04). Conclusions: Predialysis fluid overload was associated with slower gait speed and gait speed decline over time. Interventions that limit fluid overload may lead to improvements in physical performance.